2018
DOI: 10.1038/s41598-018-20026-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the origins of eastern Polynesians using genome-wide data from the Leeward Society Isles

Abstract: The debate concerning the origin of the Polynesian speaking peoples has been recently reinvigorated by genetic evidence for secondary migrations to western Polynesia from the New Guinea region during the 2nd millennium BP. Using genome-wide autosomal data from the Leeward Society Islands, the ancient cultural hub of eastern Polynesia, we find that the inhabitants’ genomes also demonstrate evidence of this episode of admixture, dating to 1,700–1,200 BP. This supports a late settlement chronology for eastern Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Indigenous populations in Remote Oceania were geographically isolated on islands that were separated by vast distances. However, genetic, linguistic, and archaeological evidence suggests that the Polynesian people of Remote Oceania maintained a complex trade network that extended from Hawaii in the north, New Zealand in the south, and Easter Island in the east (22, 23)—the so-called “Polynesian triangle.”…”
Section: Historical Peopling Of the Pacificmentioning
confidence: 99%
“…Indigenous populations in Remote Oceania were geographically isolated on islands that were separated by vast distances. However, genetic, linguistic, and archaeological evidence suggests that the Polynesian people of Remote Oceania maintained a complex trade network that extended from Hawaii in the north, New Zealand in the south, and Easter Island in the east (22, 23)—the so-called “Polynesian triangle.”…”
Section: Historical Peopling Of the Pacificmentioning
confidence: 99%
“…Tonga was not isolated, and contact with other Pacific Island populations probably occurred before the diffusion of a ‘Polynesian’ cultural package to East Polynesia c . 1000 cal BP (Wilmshurst et al 2011), as suggested by evidence that the ‘Polynesian’ genome was not fully formed until 1700–1200 BP (Hudjashov et al 2018). Thus, in addition to in situ cultural development, the arrival of new migrants after the development of Ancestral Polynesian Society probably contributed to a re-shaping of funerary practices.…”
Section: Resultsmentioning
confidence: 99%
“…Other mortuary activities that are fundamental to modern Polynesian cultural behaviour and inferred for Ancestral Polynesian Society, however, appear to have been regarded differently at Talasiu, such as the interment of bodies in an actively used midden. Tonga was not isolated, and contact with other Pacific Island populations probably occurred before the diffusion of a 'Polynesian' cultural package to East Polynesia c. 1000 cal BP (Wilmshurst et al 2011), as suggested by evidence that the 'Polynesian' genome was not fully formed until 1700-1200 BP (Hudjashov et al 2018). Thus, in addition to in situ cultural development, the arrival of new migrants after the development of Ancestral Polynesian Society probably contributed to a re-shaping of funerary practices.…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings in the field of biological anthropology are an important addition to such triangulation. Researchers have now demonstrated distinctive genetic connections in mtDNA and Y-chromosome lineages between the contemporary peoples of the Central Northern Outlier Luangiua (Ontong Java) and the Society Islands in Central East Polynesia (Hudjashov et al 2018).…”
Section: Archaeology Linguistics and Biological Anthropologymentioning
confidence: 99%
“…Mastery of longdistance voyaging to Tikopia was evident among their descendants living in the Central Northern Outliers at initial European contact (Bayliss-Smith 2012). There are also Takuu traditions of travel to Fiji and Sāmoa (Moyle 2007: 22-30;2011;2018). While other Polynesian peoples have traditions of long-distance navigation and might have been able to travel to East Polynesia and settle that huge area (Montenegro et al 2016), the peoples of the Central Northern Outliers stand out from all others in the distinctive connection between their languages and the languages of East Polynesia.…”
Section: A Borrowing Involving Tokelauanmentioning
confidence: 99%